2022
DOI: 10.1002/jaba.949
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating peer‐implemented video feedback to improve weight training form

Abstract: This study evaluated the effectiveness of behavioral skills training (BST) to teach peer-trainers to implement video feedback (Study 1) and evaluated the effectiveness of peer-implemented video feedback to increase proper deadlifting form across 3 participants (Study 2). A nonconcurrent, multiple baseline design across participants was employed to evaluate BST and peer implemented video feedback. Results demonstrate that BST was effective for teaching peertrainers to implement video feedback and video feedback… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 31 publications
5
7
0
Order By: Relevance
“…Results from this study, along with others (BenitezSantiago & Miltenberger, 2016; Cochrane et al., 2022; Kelley & Miltenberger, 2016), indicate that the use of immediate VF produced positive results for improving athletic performance. Although it seems likely that the immediacy of feedback is important, it is not clear whether the immediacy of feedback contributed to the outcome of the study.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Results from this study, along with others (BenitezSantiago & Miltenberger, 2016; Cochrane et al., 2022; Kelley & Miltenberger, 2016), indicate that the use of immediate VF produced positive results for improving athletic performance. Although it seems likely that the immediacy of feedback is important, it is not clear whether the immediacy of feedback contributed to the outcome of the study.…”
Section: Discussionsupporting
confidence: 73%
“…In another example, Cochrane et al. (2022) evaluated the effectiveness of VF alone to improve correct weight training form with the trainee's peer conducting the procedure. Following behavioral skills training to implement the VF procedure, a peer video recorded the trainee performing the target skill and immediately showed the trainee their video while providing descriptive praise and corrective feedback.…”
Section: Introductionmentioning
confidence: 99%
“…Video feedback was shown to be successful in increasing the correct behaviors for all participants. More recently, Cochrane et al (2022) showed that peer-implemented video feedback improved weightlifting form for all three participants. The researchers first used BST to train weightlifters to subsequently train three other peer weightlifters to improve their deadlift form using a task analysis and video feedback with a movement analysis software application (i.e., HudL Technique © ).…”
mentioning
confidence: 90%
“…Several behavioral interventions involving video specifically as a feedback component (opposed to an antecedent component such as video modeling) have been shown to be effective across a variety of sports (BenitezSantiago & Miltenberger, 2016;Cochrane et al, 2022;Downs et al, 2015;Kelley & Miltenberger, 2016;Snapp et al, 2023;Stokes et al, 2010). A video feedback intervention comprises two aspects: (a) the athlete and trainer review of video footage of the skill performance, and (b) the trainer supplements the video review with praise and corrective feedback to the athlete for the purposes of improving performance levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation